Rural-origin health professional students' perceptions of a support programme offered by Umthombo Youth Development Foundation - Dumisani M. Gumede; Andrew J. Ross; Laura M. Campbell; Richard G. MacGregor (AOSIS, 2017)
Background: Staffing of rural healthcare facilities is a challenge, with literature supporting the selection and training of rural-origin students. The Umthombo Youth Development Foundation (UYDF) scholarship scheme supports rural students to train as healthcare professionals and offers a unique support programme. This programme has not been evaluated, and this study sought UYDF-supported students' perceptions of the programme. Aim: The aim of the study was to assess students' perceptions of the UYDF support programme. Methods: This was an observational descriptive study. Participants were students supported by UYDF and data were collected by a questionnaire with a Likert scale to assess perceptions of various aspects of the support programme. Results: Students' perceptions about the UYDF support programme were generally positive, with initial orientation and information sharing perceived as useful. Some respondents did not perceive value in holding discussions around English proficiency. The support required appeared to diminish with increasing years of study. Conclusion: A comprehensive, proactive compulsory support system that provides both academic and social support was perceived as useful by the UYDF students. Further research is required around aspects such as encouraging English proficiency. In future, the support programme could prioritise students in the early years of their study.